The Development of Learning Activities using Storyline Method that Promotes Achievement and Retention in Learning on The Subject of History for Prathomsuksa 5 Students: The Development of Learning Activities using Storyline Method that Promotes Achievement and Retention in Learning on The Subject of History for Prathomsuksa 5 Students - Suksong, Chadaphorn; Kongkhan, Thanyaporn (RATANABUTH JOURNAL, 2023)
The objectives of this research were: 1. To create and find the efficiency of learning activities using storyline method that promotes achievement and retention in learning on the subject of history according to the 80/80 criteria. 2. Study the results of using storyline learning activities as follows: 2.1 Compare the learning achievement of Prathomsuksa 5 students with the criteria of 80%. 2.2 Study the retention of learning of students studying with storyline learning activities. The sample consisted of 24 grade 5 students obtained by cluster random sampling. The experimental period was 3 weeks. The research method was divided into 2 steps: Step 1: Creating and finding the efficiency of storyline learning activities; Step 2: Studying the results of using storyline learning activities. The statistics used for data analysis were mean ( ) , standard deviation (S.D.), t-test (one sample) and t-test (Dependent). The results showed that: Storyline learning activities consisted of 6 activities, namely activities 1. Ayutthaya kingdom 2. Important people in Ayutthaya period 3. Thai wisdom in Ayutthaya period 4. Thonburi kingdom 5. Important people in Thonburi period and 6. Wisdom Thai Thonburi period There are 7 steps in organizing activities: 1. Preparing topic 2. Preparing the subject binding 3. Setting the main question 4. The learners answer the main question 5. Class arrangement 6. Evaluation 7. Determination teaching period When taking it to inspect the quality, it was found that it was at the highest level of suitability. and the activity efficiency was 85.27/83.61 The student's academic achievement after school was higher than the 80% criterion with a statistical significance at the .05 level. The test scores after the test and the test after 2 weeks were not significantly different at the .05 level. The learners had retention in learning.